Novo inversor híbrido de cinco níveis alimentado por conversor cc-cc do tipo boost/flyback - Lacerda Filho, Antonio Venancio de Moura (2019)
The search for power converters that perform energy processing with greater efficiency and lower losses is constant in power electronics. One of the uses of these converters is in photovoltaic energy processing. The financial contribution to the micro and mini solar generation sector in Brazil has increased over the years, increasing the number of installations. This paper aims to present two new types of converters. A boost-flyback cc-cc converter made from some existing topologies and a new 5-level cc-ca inverter. The voltage generated by photovoltaic modules is of low value, being necessary the elevation to compatible levels in its application. In the case of application in an AC network, an inverter is used in series with the voltage elevator. A boost-flyback converter with two isolated outputs is integrated with a new five-level inverter to compose a system that can later be powered by photovoltaic modules. A detailed boost-flyback analysis is presented considering the ideal converter and then the component losses are considered. The study of the new hybrid inverter is presented from its design, modulation functions of the switches to obtain current efforts and conduction and switching losses. The analysis of the integrated system operating modes is presented. Finally, the simulation and experimental results are presented with the objective of validating the study.